(untitled) (Asian Journal of Medical and Biological Research, 2021)
Human papillomavirus (HPV) infection is one of the causes of cervical cancer which is preventable. The study was a cross-sectional study with the objective was to determine the Human papillomavirus (HPV) vaccination coverage among working women. A total 236 educated working women were selected purposively from different working places in Dhaka city. A pretested semi- structured questionnaire was used for data collection. The knowledge was assessed by using modified Blooms cut off points which was developed with cervical cancer and vaccine knowledge related questions. The study result revealed that among 236 working women 71.2% knew about the risk factor of cervical cancer. It was found that 92.8% knew about the way of prevention of cervical cancer respectively. The overall knowledge on cervical cancer and vaccine was found to be having good knowledge 21.2%, satisfactory knowledge 41.9% and poor knowledge 36.9%. Out of the total working women only 5.1% had HPV vaccination coverage. Reason behind non vaccinations, 50% mentioned had no knowledge about vaccine, 35.3% mentioned can’t decide and 8.9% mentioned high cost of vaccine. Significant association has been observed in between vaccination coverage with over all knowledge of cervical cancer (p value .04). It may be concluded that HPV vaccination coverage is very low which needs awareness program on this issues through mass media, educational session, counseling and so on to reduce human papillomavirus associated cancers as well as economic burden. Asian J. Med. Biol. Res. December 2020, 6(4): 714-722